Fulfillment: winning and losing in one-click America (Farrar, Straus and Giroux, Macmillan Audio, 2021)
A New York Times Book Review Editors' Choice "A grounded and expansive examination of the American economic divide . . . It takes a skillful journalist to weave data and anecdotes together so effectively." --Carolyn Kellogg, Los Angeles Times An award-winning journalist investigates Amazon's impact on the wealth and poverty of towns and cities across the United States. In 1937, the famed writer and activist Upton Sinclair published a novel bearing the subtitle A Story of Ford-America . He blasted the callousness of a company worth "a billion dollars" that underpaid its workers while forcing them to engage in repetitive and sometimes dangerous assembly line labor. Eighty-three years later, the market capitalization of Amazon.com has exceeded one trillion dollars, while the value of the Ford Motor Company hovers around thirty billion. We have, it seems, entered the age of one-click America--and as the coronavirus makes Americans more dependent on online shopping, its sway will only intensify. Alec MacGillis's Fulfillment is not another inside account or exposé of our most conspicuously dominant company. Rather, it is a literary investigation of the America that falls within that company's growing shadow. As MacGillis shows, Amazon's sprawling network of delivery hubs, data centers, and corporate campuses epitomizes a land where winner and loser cities and regions are drifting steadily apart, the civic fabric is unraveling, and work has become increasingly rudimentary and isolated. Ranging across the country, MacGillis tells the stories of those who've thrived and struggled to thrive in this rapidly changing environment. In Seattle, high-paid workers in new office towers displace a historic black neighborhood. In suburban Virginia, homeowners try to protect their neighborhood from the environmental impact of a new data center. Meanwhile, in El Paso, small office supply firms seek to weather Amazon's takeover of government procurement, and in Baltimore a warehouse supplants a fabled steel plant. Fulfillment also shows how Amazon has become a force in Washington, D.C., ushering readers through a revolving door for lobbyists and government contractors and into CEO Jeff Bezos's lavish Kalorama mansion. With empathy and breadth, MacGillis demonstrates the hidden human costs of the other inequality--not the growing gap between rich and poor, but the gap between the country's winning and losing regions. The result is an intimate account of contemporary capitalism: its drive to innovate, its dark, pitiless magic, its remaking of America with every click.

The upside of inequality: how good intentions undermine the middle class (Portfolio/Penguin, Books on Tape, Penguin Publishing Group, 2016)
The scourge of America's economy isn't the success of the 1 percent-quite the opposite. The real problem is the government's well-meaning but misguided attempt to reduce the payoffs for success. Four years ago, Edward Conard wrote a controversial bestseller, Unintended Consequences, which set the record straight on the financial crisis of 2008 and explained why U.S. growth was accelerating relative to other high-wage economies. He warned that loose monetary policy would produce neither growth nor inflation, that expansionary fiscal policy would have no lasting benefit on growth in the aftermath of the crisis, and that ill-advised attempts to rein in banking based on misplaced blame would slow an already weak recovery. Unfortunately, he was right. Now he's back with another provocative argument: that our current obsession with income inequality is misguided and will only slow growth further. Using fact-based logic, Conard tracks the implications of an economy now constrained by both its capacity for risk-taking and by a shortage of properly trained talent-rather than by labor or capital, as was the case historically. He uses this fresh perspective to challenge the conclusions of liberal economists like Larry Summers and Joseph Stiglitz and the myths of crony capitalism more broadly. Instead, he argues that the growing wealth of most successful Americans is not to blame for the stagnating incomes of the middle and working classes. If anything, the success of the 1 percent has put upward pressure on employment and wages. Conard argues that high payoffs for success motivate talent to get the training and take the risks that gradually loosen the constraints to growth. Well-meaning attempts to decrease inequality through redistribution dull these incentives, gradually hurting not just the 1 percent but everyone else as well. Conard outlines a plan for growing middle- and working-class wages in an economy with a near infinite supply of labor that is shifting from capital-intensive manufacturing to knowledge-intensive, innovation-driven fields. He urges us to stop blaming the success of the 1 percent for slow wage growth and embrace the upside of inequality: faster growth and greater prosperity for everyone.

The betrayal of the American dream (PublicAffairs, 2012)
A New York Times bestseller America's unique prosperity is based on its creation of a middle class. In the twentieth century, that middle class provided the workforce, the educated skills, and the demand that gave life to the world's greatest consumer economy. It was innovative and dynamic; it eclipsed old imperial systems and colonial archetypes. It gave rise to a dream: that if you worked hard and followed the rules you would prosper in America, and your children would enjoy a better life than yours. The American dream was the lure to gifted immigrants and the birthright opportunity for every American citizen. It is as important a part of the history of the country as the passing of the Bill of Rights, the outcome of the battle of Gettysburg, or the space program. Incredibly, however, for more than thirty years, government and big business in America have conspired to roll back the American dream. What was once accessible to a wide swath of the population is increasingly open only to aprivileged few. The story of how the American middle class has been systematically impoverished and its prospects thwarted in favor of a new ruling elite is at the heart of this extraordinarily timely and revealing book, whose devastating findings from two of the finest investigative reporters in the country will leave you astonished and angry.

The rise and fall of American growth: the U.S. standard of living since the Civil War (Princeton economic history of the Western world, ,, 2016)
How America's high standard of living came to be and why future growth is under threat In the century after the Civil War, an economic revolution improved the American standard of living in ways previously unimaginable. Electric lighting, indoor plumbing, motor vehicles, air travel, and television transformed households and workplaces. But has that era of unprecedented growth come to an end? Weaving together a vivid narrative, historical anecdotes, and economic analysis, The Rise and Fall of American Growth challenges the view that economic growth will continue unabated, and demonstrates that the life-altering scale of innovations between 1870 and 1970 cannot be repeated. Gordon contends that the nation's productivity growth will be further held back by the headwinds of rising inequality, stagnating education, an aging population, and the rising debt of college students and the federal government, and that we must find new solutions. A critical voice in the most pressing debates of our time, The Rise and Fall of American Growth is at once a tribute to a century of radical change and a harbinger of tougher times to come.

Coming apart: the state of white America, 1960-2010 (The Crown Publishing Group, Crown Forum, Blackstone Publishing, 2012)
From the bestselling author of Losing Ground and The Bell Curve, this startling long-lens view shows how America is coming apart at the seams that have historically joined our classes. In Coming Apart, Charles Murray explores the formation of American classes that are different in kind from anything we have ever known, focusing on whites as a way of driving home the fact that the trends he describes do not break along lines of race or ethnicity. Drawing on five decades of statistics and research, Coming Apart demonstrates that a new upper class and a new lower class have diverged so far in core behaviors and values that they barely recognize their underlying American kinship-a divergence that has nothing to do with income inequality and that has grown during good economic times and bad. The top and bottom of white America increasingly live in different cultures, Murray argues, with the powerful upper class living in enclaves surrounded by their own kind, ignorant about life in mainstream America, and the lower class suffering from erosions of family and community life that strike at the heart of the pursuit of happiness. This divergence puts the success of the American project at risk. The evidence in Coming Apart is about white America. Its message is about all of America.

Aftershock: the next economy and America's future (Alfred A. Knopf, Knopf Doubleday Publishing Group, Playaway Digital Audio, [Manufactured by] Findaway World, LLC, [Distributed exclusively by] Recorded Books, LLC, 2011)
The author of 12 acclaimed books, Robert B. Reich is a Chancellor's Professor of Public Policy at the University of California, Berkeley, and has served in three national administrations. While many blamed Wall Street for the financial meltdown, Aftershock points a finger at a national economy in which wealth is increasingly concentrated at the top-and where a grasping middle class simply does not have the resources to remain viable.

The big short: inside the doomsday machine (Simon & Schuster Audio, W.W. Norton, W. W. Norton & Company, W.W. Norton & Co, Thorndike Press, 2011)
The #1 New York Times bestseller: a brilliant account--character-rich and darkly humorous--of how the U.S. economy was driven over the cliff. When the crash of the U. S. stock market became public knowledge in the fall of 2008, it was already old news. The real crash, the silent crash, had taken place over the previous year, in bizarre feeder markets where the sun doesn't shine, and the SEC doesn't dare, or bother, to tread: the bond and real estate derivative markets where geeks invent impenetrable securities to profit from the misery of lower- and middle-class Americans who can't pay their debts. The smart people who understood what was or might be happening were paralyzed by hope and fear; in any case, they weren't talking. The crucial question is this: Who understood the risk inherent in the assumption of ever-rising real estate prices, a risk compounded daily by the creation of those arcane, artificial securities loosely based on piles of doubtful mortgages? Michael Lewis turns the inquiry on its head to create a fresh, character-driven narrative brimming with indignation and dark humor, a fitting sequel to his #1 best-selling Liar's Poker . Who got it right? he asks. Who saw the real estate market for the black hole it would become, and eventually made billions of dollars from that perception? And what qualities of character made those few persist when their peers and colleagues dismissed them as Chicken Littles? Out of this handful of unlikely--really unlikely--heroes, Lewis fashions a story as compelling and unusual as any of his earlier bestsellers, proving yet again that he is the finest and funniest chronicler of our times.

The affluent society (Houghton Mifflin, 1998)
John Kenneth Galbraith's classic investigation of private wealth and public poverty in postwar America. With customary clarity, eloquence, and humor, Harvard economist John Kenneth Galbraith gets at the heart of what economic security means in The Affluent Society. Warning against individual and societal complacence about economic inequity, he offers an economic model for investing in public wealth that challenges "conventional wisdom" (a phrase he coined that has since entered our vernacular) about the long-term value of a production-based economy and the true nature of poverty. Both politically divisive and remarkably prescient, The Affluent Society is as relevant today on the question of wealth in America as it was in 1958.

World made by hand (World made by hand, 1, 1, 2009)
In the best-seller The Long Emergency , James Howard Kunstler explored how the terminal decline of oil production had the potential to put industrial civilization out of business. With World Made By Hand Kunstler makes an imaginative leap into the future, a few decades hence, and shows us what life may be like after these coming catastrophes--the end of oil, climate change, global pandemics, and resource wars--converge. For the townspeople of Union Grove, New York, the future is not what they thought it would be. Transportation is slow and dangerous, so food is grown locally at great expense of time and energy. And the outside world is largely unknown. There may be a president and he may be in Minneapolis now, but people aren't sure. As the heat of summer intensifies, the residents struggle with the new way of life in a world of abandoned highways and empty houses, horses working the fields and rivers replenished with fish. A captivating, utterly realistic novel, World Made by Hand takes speculative fiction beyond the apocalypse and shows what happens when life gets extremely local.

Trump, the blue-collar president (Hachette Audio, Center Street, 2018)
In an administration not known for its subtlety, no comet soared higher, burned brighter, or flamed out more spectacularly than Anthony Scaramucci. For eleven days (not ten, as widely reported, he'll tell anyone who'll listen) he ran the most important communications department in the world, the White House's. By the end of his short tenure -- several of the most tumultuous and formative days of the Trump administration -- he'd gone from a fairly well known on-air surrogate for the president to a household name, "the Mooch." The rise and fall of the Mooch, which riveted the nation, unfolded like a Shakespearean play directed by Martin Scorsese. In his own inimitable voice, Anthony reveals the juicy details behind his stormy term as White House communications director. He holds nothing back and spares no one's feelings-including those of the country's most powerful people. If political movements are best understood through a single human life, then there is no better life to tell the story of Donald Trump's rise in America than the Mooch's. From Long Island Newsday paperboy, with the largest route in Port Washington, to Master of the Universe, as Tom Wolfe characterized his kind in Bonfire of the Vanities, Anthony's life was the embodiment of the American Dream. By his own admission, however, he became so involved in his high-octane career and life that he forgot his working-class roots. He wasn't the only one to ignore the working class. There were neighborhoods like the one he grew up in throughout the country filled with deflated, unemployed, or underpaid people, ignored by elites and politicians-until Donald Trump came along. It was only when Anthony joined the Donald Trump for President campaign as a surrogate and economic advisor that his eyes were opened to the plight of our country's middle class. It took a billionaire real estate developer who lived in a tower on Fifth Ave to show him what had happened to the neighborhood in which he'd grown up and communities like it throughout America. It was then that Anthony realized that Donald Trump and his economic policies were the best bet for our country's future. A romp of a read, by turns hilarious, touching, and inspiring, Trump, the Blue-Collar President is sure to be among the best books written about the Trump presidency.

The imperious economy (Harvard University Press, 1982)
Description Not Provided

Crash: the Great Depression and the fall and rise of America (Little, Brown and Company, 2018)
The incredible true story of how real people weathered one of the most turbulent periods in American history--the Great Depression--and emerged triumphant. From the sweeping consequences of the stock market crash to the riveting stories of individuals and communities caught up in a real American dystopia, discover how the country we live in today was built in response to a time when people from all walks of life fell victim to poverty, insecurity, and fear. Meet fascinating historical characters like Herbert Hoover, Franklin Delano and Eleanor Roosevelt, Frances Perkins, Dorothea Lange, Walter White, and Mary McLeod Bethune. See what life was like for regular Americans as the country went from the highs of the Roaring Twenties to the lows of the Great Depression, before bouncing back again during World War II. Explore pivotal scenes such as the creation of the New Deal, life in the Dust Bowl, the sit-down strikes in Michigan, the Scottsboro case, and the rise of Father Coughlin. Packed with photographs and firsthand accounts, and written with a keen understanding of the upheaval of the 1930s, Crash shares the incredible story of how America survived--and, ultimately, thrived.

Americana: a 400-year history of American capitalism (Penguin Publishing Group, Books on Tape, Penguin Press, 2017)
An absorbing and original narrative history of American capitalism NAMED A BEST BOOK OF 2017 BY THE ECONOMIST From the days of the Mayflower and the Virginia Company, America has been a place for people to dream, invent, build, tinker, and bet the farm in pursuit of a better life. Americana takes us on a four-hundred-year journey of this spirit of innovation and ambition through a series of Next Big Things -- the inventions, techniques, and industries that drove American history forward: from the telegraph, the railroad, guns, radio, and banking to flight, suburbia, and sneakers, culminating with the Internet and mobile technology at the turn of the twenty-first century. The result is a thrilling alternative history of modern America that reframes events, trends, and people we thought we knew through the prism of the value that, for better or for worse, this nation holds dearest: capitalism. In a winning, accessible style, Bhu Srinivasan boldly takes on four centuries of American enterprise, revealing the unexpected connections that link them. We learn how Andrew Carnegie's early job as a telegraph messenger boy paved the way for his leadership of the steel empire that would make him one of the nation's richest men; how the gunmaker Remington reinvented itself in the postwar years to sell typewriters; how the inner workings of the Mafia mirrored the trend of consolidation and regulation in more traditional business; and how a 1950s infrastructure bill triggered a series of events that produced one of America's most enduring brands: KFC. Reliving the heady early days of Silicon Valley, we are reminded that the start-up is an idea as old as America itself. Entertaining, eye-opening, and sweeping in its reach, Americana is an exhilarating new work of narrative history.

The American economy from the great crash to the Third Industrial Revolution (Harlan Davidson, 1992)
The first seven chapters of this book discuss the important developments and events since 1929. Business, labour, agriculture, and government policy receive frequent attention as do the key individuals who shaped the past. Chapters eight and nine discuss present issues: the legacy of deregulation, the overburdened infrastructure, environmental abuse, urban problems, and health care expenses. The last two chapters discuss what the author calls the Third Industrial Revolution, the changes created by microprocessors, lasers, fibre optics, biogenetics, etc; the author believes this transformation will be given more profound than the First Industrial Revolution (which ushered in the machine age at the beginning of the 19th century) or the Second (the age of the automobile, electricity, radio, and large-scale chemical production).

The fifties (Villard Books, Open Road Media, 1993)
The Fifties is a sweeping social, political, economic, and cultural history of the ten years that Halberstam regards as seminal in determining what our nation is today. Halberstam offers portraits of not only the titans of the age: Eisenhower Dulles, Oppenheimer, MacArthur, Hoover, and Nixon, but also of Harley Earl, who put fins on cars; Dick and Mac McDonald and Ray Kroc, who mass-produced the American hamburger; Kemmons Wilson, who placed his Holiday Inns along the nation's roadsides; U-2 pilot Gary Francis Powers; Grace Metalious, who wrote Peyton Place; and "Goody" Pincus, who led the team that invented the Pill. A NEW YORK TIMES BESTSELLER

The hidden cost of being African American: how wealth perpetuates inequality (Oxford University Press, 2004)
Description Not Provided

The Thomas Sowell reader ([Manufactured and distributed by] Findaway World, LLC, Basic Books, Playaway Digital Audio, 2011)
These selections from the many writings of Thomas Sowell over a period of half a century cover social, economic, cultural, legal, educational, and political issues. The sources range from Dr. Sowell's letters, books, newspaper columns, and articles in both scholarly journals and popular magazines. The topics range from late-talking children to tax cuts for the rich, baseball, race, war, the role of judges, medical care, and the rhetoric of politicians. These topics are dealt with by drawing sometimes on history, sometimes on economics, and sometimes on a sense of humor.

The rich and the rest of us: a poverty manifesto (Hay House, Smiley Books, 2012)
Record unemployment and rampant corporate avarice, empty houses but homeless families, dwindling opportunities in an increasingly paralyzed nation--these are the realities of 21st-century America, land of the free and home of the new middle class poor. Award-winning broadcaster Tavis Smiley and Dr. Cornel West, one of the nation's leading democratic intellectuals, co-hosts of Public Radio's Smiley & West , now take on the "P" word--poverty.The Rich and the Rest of Us is the next step in the journey that began with "The Poverty Tour: A Call to Conscience." Smiley and West's 18-city bus tour gave voice to the plight of impoverished Americans of all races, colors, and creeds. With 150 million Americans persistently poor or near poor, the highest numbers in over five decades, Smiley and West argue that now is the time to confront the underlying conditions of systemic poverty in America before it's too late.By placing the eradication of poverty in the context of the nation's greatest moments of social transformation-- such as the abolition of slavery, woman's suffrage, and the labor and civil rights movements--ending poverty is sure to emerge as America's 21st -century civil rights struggle.As the middle class disappears and the safety net is shredded, Smiley and West, building on the legacy of Martin Luther King, Jr., ask us to confront our fear and complacency with 12 poverty changing ideas. They challenge us to re-examine our assumptions about poverty in America--what it really is and how to eliminate it now.

Heaven's door: immigration policy and the American economy (Princeton University Press, 1999)
The U.S. took in more than a million immigrants per year in the late 1990s, more than at any other time in history. For humanitarian and many other reasons, this may be good news. But as George Borjas shows in Heaven's Door , it's decidedly mixed news for the American economy--and positively bad news for the country's poorest citizens. Widely regarded as the country's leading immigration economist, Borjas presents the most comprehensive, accessible, and up-to-date account yet of the economic impact of recent immigration on America. He reveals that the benefits of immigration have been greatly exaggerated and that, if we allow immigration to continue unabated and unmodified, we are supporting an astonishing transfer of wealth from the poorest people in the country, who are disproportionately minorities, to the richest. In the course of the book, Borjas carefully analyzes immigrants' skills, national origins, welfare use, economic mobility, and impact on the labor market, and he makes groundbreaking use of new data to trace current trends in ethnic segregation. He also evaluates the implications of the evidence for the type of immigration policy the that U.S. should pursue. Some of his findings are dramatic: Despite estimates that range into hundreds of billions of dollars, net annual gains from immigration are only about $8 billion. In dragging down wages, immigration currently shifts about $160 billion per year from workers to employers and users of immigrants' services. Immigrants today are less skilled than their predecessors, more likely to re-quire public assistance, and far more likely to have children who remain in poor, segregated communities. Borjas considers the moral arguments against restricting immigration and writes eloquently about his own past as an immigrant from Cuba. But he concludes that in the current economic climate--which is less conducive to mass immigration of unskilled labor than past eras--it would be fair and wise to return immigration to the levels of the 1970s (roughly 500,000 per year) and institute policies to favor more skilled immigrants.

Ours was the shining future: the story of the American dream (Random House, Random House Publishing Group, Books on Tape, 2023)
The clear-eyed, definitive history of the modern American economy and the decline of the American Dream, from the Pulitzer Prize-winning columnist behind The New York Times's "The Morning" newsletter. "With the even-handed incisiveness that has made him one of the country's most-respected voices on economics, David Leonhardt illuminates the inside history of the players and missteps that have stolen so many Americans' futures."--Jane Mayer, author of Dark Money NEW YORK TIMES BOOK REVIEW EDITORS' CHOICE * ONE OF THE ATLANTIC 'S TEN BEST BOOKS OF THE YEAR * A FINANCIAL TIMES BEST BOOK OF THE YEAR Two decades into the twenty-first century, the stagnation of living standards has become the defining trend of American life. Life expectancy has declined, economic inequality has soared, and, after some progress, the Black-white wage gap is once again as large as it was in the 1950s. How did this happen in the world's most powerful country? And what happened to the "American dream"--the promise of a happier, healthier, more prosperous future--which was once such an inextricable part of our national identity? Drawing on decades of writing about the economy for The New York Times, Pulitzer Prize-winning writer David Leonhardt examines the past century of American history, from the Great Depression to today's Great Stagnation, in search of an answer. To make sense of the rise and subsequent fall of the American dream, Leonhardt tells the story of the modern American economy as an ongoing battle between two competing forms of capitalism: one that envisions prosperity for most, and one that serves the individual and favors the wealthy. In vivid prose, Ours Was the Shining Future traces how democratic capitalism flourished to make the American dream possible, until the latter decades of the twentieth century when, bit by bit, the dream was corrupted to serve only the privileged few. Ours Was the Shining Future is a sweeping narrative full of innovation and grit, human drama and hope. Featuring the trailblazing figures who helped shape the American dream--Frances Perkins, Paul Hoffman, Cesar Chavez, Robert Kennedy, A. Philip Randolph, Grace Hopper, and more--this engaging history reveals the power of grassroots democratic movements from across the political spectrum. And though the American dream feels lost to us now, Leonhardt shows how Americans--if they commit themselves to transforming the economy, as they did in the past--have the power to revive the dream once more.